Is the recurrence of primary spontaneous pneumothorax predictable? - Saricam, Murat (International Journal of Advances in Medicine, 2019)
Background: Recurrence of Primary Spontaneous Pneumothorax (PSP) constitutes a serious challenge for both physicians and patients. Methods: A retrospective study was conducted in 115 patients who had chest tubes at their first onset of PSP. Considering the development of recurrence, two groups were composed and comparatively examined in terms of age, body mass index, smoking status, side and size of initial pneumothorax, presence of bulla and duration of chest tube drainage at the first episode. Results: Among 115 patients with PSP, 24 cases developed recurrence. Male gender was prominently relevant to develop recurrent PSP (p=0.034) whereas remaining inspected parameters revealed no significant relationship with a relapse. Interval between first onset and recurrence of PSP was calculated as 9.2 months. Interestingly, most of the patients developed recurrence in low-temperature months. Conclusions: Recurrence of PSP is substantially unpredictable. Therefore, close follow-up of cases in the following year of their first episode and also informing the patients about probability of a relapse and measures to consider under this circumstance is of great importance.